2022
DOI: 10.3389/fcell.2022.827691
|View full text |Cite
|
Sign up to set email alerts
|

Putative Prevention of XML Injection Against Myocardial Ischemia Is Mediated by PKC and PLA2 Proteins

Abstract: Background: Xinmailong (XML) injection is a CFDA-approved traditional Chinese medicine with clinical value for heart failure treatment. The present investigation was aimed to evaluate the potential protective roles of this injection on myocardial ischemia and the underlying molecular mechanism.Methods: In our study, we selected two models of myocardial ischemia rats. Rats were randomly divided into six groups, with saline or XML administrated 4 days before ischemia model establishment. ECG of different time in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Caspase-9 is a promoter and participates in the apoptosis process after activation [ 67 ]. Xinmailong exerts protective effects against myocardial injury by increasing the expression of Bcl-2 and decreasing the expression of Bax [ 68 ]. Trimetazidine can increase myocardial function by decreasing the expression of apoptotic proteins, such as Bax and caspase-3, and reducing myocardial infarct size [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-9 is a promoter and participates in the apoptosis process after activation [ 67 ]. Xinmailong exerts protective effects against myocardial injury by increasing the expression of Bcl-2 and decreasing the expression of Bax [ 68 ]. Trimetazidine can increase myocardial function by decreasing the expression of apoptotic proteins, such as Bax and caspase-3, and reducing myocardial infarct size [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies involving HFpEF patients have demonstrated that Xinmailong injection can alleviate inflammation by reducing BNP, high‐sensitivity C‐reactive protein, and procalcitonin levels [74, 75]. In animal experiments, Xinmailong injection has been shown to protect against myocardial damage by reducing ROS production, apoptosis, and inflammation [87].…”
Section: Treatment For Hf By Itcwmmentioning
confidence: 99%
“…Xinmailong injection (XMLI) is a composite peptide injection extracted from Periplaneta americana L, containing adenosine, inosine, protocatechuic acid, and pyroglutamyl dipeptide as its main active ingredients ( Qi et al, 2017 ). Modern pharmacological studies have elucidated the cardioprotective properties of XMLI, notably in inhibiting oxidative stress ( Jiang et al, 2021 ) and inflammatory response ( Jin et al, 2022 ), regulating cell autophagy ( Li et al, 2016 ), and modulating cytokine expression ( Liu et al, 2017 ). Jiang et al ( Jiang et al, 2021 ) observed that XMLI modulates HO-1 mediated lysosomal function and autophagy in H9C2 cells, reduces oxidative stress and mitigates DOX-induced cardiac toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al ( Jiang et al, 2021 ) observed that XMLI modulates HO-1 mediated lysosomal function and autophagy in H9C2 cells, reduces oxidative stress and mitigates DOX-induced cardiac toxicity. Jin et al ( Jin et al, 2022 ) revealed that XMLI can reduce ROS production, minimize inflammatory response, and decrease cell apoptosis by improving PKC and PLA2 protein-mediated myocardial ischemia. Li et al ( Li et al, 2016 ) demonstrated that XMLI targets autophagy by activating the PI3K/Akt pathway and inhibiting Erk1/2 and P38 MAPK pathways, effectively alleviating epirubicin-induced cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%